Epac1 Is Crucial for Maintenance of Endothelial Barrier Function through A Mechanism Partly Independent of Rac1 - García-Ponce, Alexander (Cells, 2020)
Epac1 (exchange protein activated by cAMP) stabilizes the endothelial barrier, but detailed studies are limited by the side effects of pharmacological Epac1 modulators and transient transfections. Here, we compare the key properties of barriers between endothelial cells derived from wild-type (WT) and Epac1-knockout (KO) mice myocardium. We found that KO cell layers, unlike WT layers, had low and cAMP-insensitive trans-endothelial resistance (TER). They also had fragmented VE-cadherin staining despite having augmented cAMP levels and increased protein expression of Rap1, Rac1, RhoA, and VE-cadherin. The simultaneous direct activation of Rac1 and RhoA by CN04 compensated Epac1 loss, since TER was increased. In KO-cells, inhibition of Rac1 activity had no additional effect on TER, suggesting that other mechanisms compensate the inhibition of the Rac1 function to preserve barrier properties. In summary, Epac1 is crucial for baseline and cAMP-mediated barrier stabilization through mechanisms that are at least partially independent of Rac1.